The health costs of ethnic distance: Evidence from Sub-Saharan Africa - Joseph Flavian Gomes (University of Essex, Institute for Social and Economic Research (ISER), 2014)
We show that ethnic distances can explain the ethnic inequalities in child mortality rates in Africa. Using individual level micro data from DHS surveys for fourteen Sub-Saharan African countries combined with a novel high resolution dataset on the spatial distribution of ethnic groups we show that children whose mothers have a higher linguistic distance from their neighbours have a higher probability of dying. Fractionalization reduces the probability of child death. We argue that fractionalization re ects a higher stock of knowledge and information leading to better health outcomes. Knowledge does not ow smoothly to linguistically distant groups. Linguistically distant mothers also have a lower probability of knowing about the oral rehydration product (ORS) for treating children with diarrhoea.
Keywords: I14; O10; 330; child mortality; ethnic inequality; ethnic/linguistic distance; ethno-linguistic diversity; health inequalities